Glutathione: antioxidant defense and regulation of its synthesis - Forman, Henry Jay (Henry Stewart Talks, 2007)
Glutathione, Glutathione in protection, Sources of oxidants and electrophiles, Elimination of oxidants and other electrophiles by glutathione, Assessment of glutathione status, Synthesis of glutathione (pathway), Synthesis of glutathione (regulation)
Reviewed at 2018/06/28